PENERAPAN ASAS UNUS TESTIS NULLUS TESTIS DAN TESTIMONIUM DE AUDITU DALAM SISTEM PEMBUKTIAN DI PERADILAN MILITER TERHADAP PERKARA TINDAK PIDANA ASUSILA - Muchamad Nur Adnan; Nandang Sambas (Iustitia Omnibus (Jurnal Ilmu Hukum), 2021)
ABSTRACT Witnesses who stand alone cannot be used as evidence, unless there is agreement with other evidence. This principle is one witness is not witness or known as unus testis nullus testis. In practice, there is a decision by the Panel of Judges that does not adhere to the principles of criminal procedural law. The research method used is descriptive analytical approach and normative juridical research specification While the data analysis used a qualitative juridical method. From the results of the authors research, the decision oh the Supreme Court Number 134 K/Mil/2015 does not apply the principle of unus testis nullus testis and the witness evidence presented by the Military Prosecutor and the reporting party has no evidentiary power because the are witness of testimony de auditu Keyword : Unus testis nullus testis, Testimonium de auditu, Military Courts, Immoral crime